Detecting and avoiding plagiarism in an academic context: description of a project developed within an undergraduate course in Information Science - Terra, Ana Lúcia (2021)
A proposal for an intervention project to avoid academic plagiarism settled, using a project-based learning approach, in a curricular unit of an Information Science undergraduate course is presented. Theoretical context is based on a literature review on the concept of plagiarism and on digital tools for detecting plagiarism. The methodology and objectives of the project to detect and avoid plagiarism are described, and the outputs from its implementation are presented. Special emphasis is placed on the identification, analysis and evaluation of 10 digital plagiarism detection tools, based on a grid of criteria defined for this purpose. This procedure resulted in the selection of the three best tools (PlagScan, Urkund and Plag.pt), which are presented in more detail. In addition, materials designed to be used in a strategy to avoid plagiarism in an academic community are presented. The relevance of the work is based on the testimony of innovative didactic practices in an Information Science graduate course, through the use of project-based learning. The spreading and evaluation of plagiarism detection tools, framed in a broader strategy to fight plagiarism in an academic environment, is also a relevant output of this paper.